Comparisons of Natural and Cultivated Populations of Corydalis yanhusuo Indicate Divergent Patterns of Genetic and Epigenetic Variation - Chen, Chen; Zheng, Zhi; Bao, Yiqiong; Zhang, Hanchao; Richards, Christina L.; Li, Jinghui; Chen, Yahua; Zhao, Yunpeng; Shen, Zhenguo; Fu, Chengxin (Frontiers in Plant Science, 2020)
Epigenetic variation may contribute to traits that are important in domestication, but how patterns of genetic and epigenetic variation differ between cultivated and wild plants remains poorly understood. In particular, we know little about how selection may shape epigenetic variation in natural and cultivated populations. In this study, we investigated 11 natural populations and 6 major cultivated populations using amplified fragment length polymorphism (AFLP) and methylation-sensitive AFLP (MS-AFLP or MSAP) markers to identify patterns of genetic and epigenetic diversity among Corydalis yanhusuo populations. We further explored correlations among genetic, epigenetic, alkaloidal and climatic factors in natural and cultivated C. yanhusuo. We found support for a single origin for all cultivated populations, from a natural population which was differentiated from the other natural populations. The magnitude of FST based on AFLP was significantly correlated with that for MSAP in pairwise comparisons in both natural and cultivated populations, suggesting a relationship between genetic and epigenetic variation in C. yanhusuo. This relationship was further supported by dbRDA (distance-based redundancy analyses) where some of the epigenetic variation could be explained by genetic variation in natural and cultivated populations. Genetic variation was slightly higher in natural than cultivated populations, and exceeded epigenetic variation in both types of populations. However, epigenetic differentiation exceeded that of genetic differentiation among cultivated populations, while the reverse was observed among natural populations. The differences between wild and cultivated plants may be partly due to processes inherent to cultivation and in particular the differences in mode of reproduction. The importance of epigenetic compared to genetic modifications is thought to vary depending on reproductive strategies, and C. yanhusuo usually reproduces sexually in natural environments, while the cultivated C. yanhusuo are propagated clonally. In addition, alkaloid content of C. yanhusuo varied across cultivated populations, and alkaloid content was significantly correlated to climatic variation, but also to genetic (6.89%) and even more so to epigenetic (14.09%) variation in cultivated populations. Our study demonstrates that epigenetic variation could be important in cultivation of C. yanhusuo and serve as a source of variation for response to environmental conditions.